Análisis de la eficiencia productiva de la piladora San Francisco del Recinto Pueblo Nuevo - Cevallos Paredes, Holger Josue (2021)
The purpose of carrying out this research is to carry out an analysis of the productive efficiency of the Piladora "San Francisco", using the line of research information and communication systems, entrepreneurship and innovation and the subline local development and sustainable and sustainable entrepreneurship. The objective of productivity is to measure the efficiency of production for each factor or resource used, understanding by efficiency the fact of obtaining the best or maximum performance using a minimum of resources. This research allowed us to know that the city of Babahoyo has the best commercial link in the province due to its high-scale agriculture and its high-quality crops. The vast majority of the population is dedicated to cultivation, mainly rice, bananas and cocoa. Thanks to the analysis of the results obtained by observing the financial statements of the pile machine, it was possible to know the level of productivity and efficiency of this company.